2018
DOI: 10.1002/jcp.27495
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation as biomarkers for diagnosis of melanoma: A systematic review and meta‐analysis

Abstract: Melanoma is one of the most common skin cancer that is characterized by rapid growth, early metastasis, high malignant, and mortality. Accumulating evidence demonstrated that promoter methylation of tumor-suppressor genes is implicated in the pathogenesis of melanoma. In the current study, we performed a meta-analysis to identify promising methylation biomarkers in the diagnosis of melanoma. We carried out a systematic literature search using Pubmed, Embase, and ISI web knowledge database and found that gene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Hypermethylation has been associated to the silencing of genes and to decreased gene expression of tumour suppressors, whilst hypomethylation can potentially result in genomic instability and reactivation of oncogenes (Litovkin et al 2014(Litovkin et al , 2015Paska and Hudler 2015;Weisenberger 2014). Based on genome-wide studies, abnormal methylation patterns have been detected in melanoma patients, highlighting potential markers for disease progression and also providing an important strategy for tumour diagnosis and treatment (Fu et al 2017;Guo et al 2018;Koga et al 2009). Nevertheless, as the proteome represents a link between DNA and phenotype, proteins likely provide a more accurate depiction of the cell state.…”
Section: Linking Genes To Protein Expression and Functionmentioning
confidence: 99%
“…Hypermethylation has been associated to the silencing of genes and to decreased gene expression of tumour suppressors, whilst hypomethylation can potentially result in genomic instability and reactivation of oncogenes (Litovkin et al 2014(Litovkin et al , 2015Paska and Hudler 2015;Weisenberger 2014). Based on genome-wide studies, abnormal methylation patterns have been detected in melanoma patients, highlighting potential markers for disease progression and also providing an important strategy for tumour diagnosis and treatment (Fu et al 2017;Guo et al 2018;Koga et al 2009). Nevertheless, as the proteome represents a link between DNA and phenotype, proteins likely provide a more accurate depiction of the cell state.…”
Section: Linking Genes To Protein Expression and Functionmentioning
confidence: 99%
“…Due to the lack of direct genetic components in transcriptional reprogramming, studying the epigenetic factors that may promote cellular plasticity leading to increased invasion and metastasis is reasonable . Based on the Cancer Genome Atlas Network (TCGA), the well‐established mutational classifications of melanomas are not in agreement with gene expression patterns, which could explain not only the low response rate of therapies targeting the aforementioned mutations but also the concerns raised against the durability of such interventions .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Guo et al found up to 50 genes, associated with risk of melanoma, in the context of promoter methylation. 6 Moreover, hypomethylation-mediated inactivation of CLDN11 is reported in melanoma. Hypermethylation of tumor-related genes such as RASSF1A, 47 APC, 48 DAPK 49 HOXB13, 50 MGMT, 18 WIF1, 51 RARB, 19 INK4A, 52 SYK, 53 TFPI2 41 and SOCS1 54 are found to be associated with advanced melanoma and poor prognosis.…”
Section: Dna Methylation In Melanomamentioning
confidence: 99%
“…3 Skin cancers are one of the most prevalent groups of cancersthe two broad groups being melanoma and non-melanoma cancers. [4][5][6] Melanoma is the 19 th most commonly occurring cancer in men and women, with about 300,000 new cases reported in 2018. 7 Although melanoma accounts for a smaller percentage of all skin cancers when compared to nonmelanoma cancers, it is the cause for most skin cancer-related deaths.…”
Section: Introductionmentioning
confidence: 99%